Does moonlighting influence South African nurses' intention to leave their primary jobs? - Laetitia C. Rispel; Tobias Chirwa; Duane Blaauw (Taylor & Francis Group, 2014)
Background: Staff retention and turnover have risen in prominence in the global discourse on the health workforce. Moonlighting, having a second job in addition to a primary job, has not featured in debates on turnover. Objective: This paper examines whether moonlighting is a determinant of South African nurses' intention to leave their primary jobs. Design: During 2010, a one-stage cluster random sample of 80 hospitals was selected in four South African provinces. On the survey day, all nurses working in critical care, theatre, emergency, maternity, and general medical and surgical wards completed a self-administered questionnaire after giving informed consent. In addition to demographic information and information on moonlighting, the questionnaire obtained information on the participants' intention to leave their primary jobs in the 12 months following the survey. A weighted analysis of the survey data was done using STATA® 13. Results: Survey participants (n=3,784) were predominantly middle-aged with a mean age of 41.5 (SD±10.4) years. Almost one-third of survey participants (30.9%) indicated that they planned to leave their jobs within 12 months. Intention to leave was higher among the moonlighters (39.5%) compared to non-moonlighters (27.9%; p<0.001). Predictors of intention to leave in a multiple logistic regression were moonlighting in the preceding year, nursing category, sector of primary employment, period working at the primary job, and number of children. The odds of intention to leave was 1.40 (95% CI: 1.16-1.69) times higher for moonlighters than for non-moonlighters. The odds ratio of intention to leave was 0.53 (95% CI: 0.42-0.66) for nursing assistants compared to professional nurses and 2.09 (95% CI: 1.49-2.94) for nurses working for a commercial nursing agency compared to those working in the public sector. Conclusions: Moonlighting is a predictor of intention to leave. Both individual and organisational strategies are needed to manage moonlighting and to enhance retention among South African nurses.